Norway’s involvement in the transatlantic slave trade: a discourse analysis of media coverage and implications for education - Paul Thomas; Jocelyne Von Hof (Cogent Social Sciences)
This study explored the Norwegian media’s coverage (2015-2022) of the discovery of the wreck of a slave ship in 1974 and how this coverage related to contemporary antiracist issues such as Black Lives Matter, the Rhodes Must Fall movement, and the murder of George Floyd. A content analysis was applied to 16 of a total of 24 newspaper articles (online and print versions) informed by critical discourse analysis and tenets of critical race theory. Findings indicate that the overarching objective appears to be documenting the facticity of the Danish-Norwegian slave trade, with a particular focus on the significant role played by Norwegians. The journalists assume the role of archaeologists in making a historical inventory of this epoch. It is argued that, while the above is laudable given the miasma of ignorance surrounding the role of Norwegians in the slave trade, the coverage fails to take cognizance of the over 11% of black and brown Norwegians of African and Asian extraction in whose eyes Norwegian culpability in the slave trade is treated as an isolated compartmentalized historical event dislocated from contemporary antiracist struggles and the racial microaggressions of the everyday that are left unaddressed.